Study of Nonlinear Behavior in Steel Shear Connections via Finite Element Modeling - Sagar, Ishwar Chandra Vidya; Bilhassan, Salima (Journal of Progress in Civil Engineering, 2025)
Shear-links are the most important part of an eccentrically braced steel frame system and provide fuse in terms of reducing the forces acting on the rest of the members such as columns and braces in the framing system. In this study shear links are modeled and analyzed in finite element program ANSYS Workbench with 3-D elements. The study is attempted to increase strength, reduce weight and produce more economical structures by using elegant member sections. Shear links with different sections are modeled, analyzed and find out optimal section. By grid convergence study finds out the optimal element length needed for the shear links under various loading conditions. Nonlinear analysis of shear links with the influence of unsymmetrical loading is to be carried out and analyze the models with weight and stress parameters.